The Political Economy of Infrastructure Investment in India - Chetan Ghate (Max Planck Institute of Economics, 2007)
We construct a simple political economy model with imperfect capital markets to explain infrastructure investments across Indian states. The model predicts that: i) the fixed cost of accessing the modern sector, ii) the initial stock of infrastructure, iii) median voter wealth, and iv) corruption, can all potentially explain why different states have different level of infrastructure investments. The theoretical model is motivated by recent empirical work on India that argues that there as on why per capita income across Indian states have diverged is because of the distribution of infrastructure investments. The model suggests that reducing leakages in funds earmarked for infrastructure and reducing the ?xed costs of accessing the modern sector - beyond their other well known effects - are policy complements. Together, they can incentivize politicians to spend more on infrastructure.
Keywords: P16; E62; O40; 330; Public investment; positive political economy; median voter theorem; Infrastrukturinvestition; Teilstaat; Public Choice; Regionale Entwicklung; Regionale Disparität; Median Voter; Indien